Huygens's understanding of trajectory: Via media between Galileo and Newton - Ducheyne, Steffen (Historia scientiarum, International Journal of the History of Science Society of Japan, 2007)
In this essay, I shall argue that Huygens can be truly seen as the via media between Galileo and Newton as far as conceptualizing orbital motion is concerned. Contrary to Galileo (who endorsed a concept of circular inertia when dealing with orbital motion), Huygens subscribed to our modern idea of rectilinear motion. Huygens was unable to integrate adequately in his worldview of vortical mechanics. However, he was aware of the utter importance of studying nascent motions (as Joella G. Yoder has pointed out before) It will be shown that an adequate account of orbital motion required three necessary ingredients: (1) an adequate conceptual framework (rectilinear inertia), (2) a fruitful metaphysical outlook (the existence of voids) and an appropriate mathematical machinery (with a focus on nascent motion). All three components were successfully put to practice by Newton.